Feasibility of Cryopreserved Conduits for Complex Vascular Reconstruction in the Pediatric Population: The Case of a 3-Year-Old With Femoral Vessels Transections. (October 2018) - Bonasso, Patrick C.; d'Audiffret, Alexandre; Vaughan, Richard; Pillai, Lakshmikumar
This report presents an unusual case of traumatic iliofemoral vessel transection in a 3-year-old patient successfully reconstructed using a cryopreserved greater saphenous conduit. Five years after injury, the patient continues to do well with normal ambulation. An arterial duplex demonstrated graft patency free of aneurysmal dilatation. These encouraging results suggest that the natural history of cryopreserved conduits may differ in the pediatric population and cryopreserved conduits could be used for complex vascular reconstructions.